Screening for STIs among criminal legal system involved youth of color in community settings - Alwyn Cohall; Renee Cohall; Laura Staeheli; Curtis Dolezal; Stephanie Campos; Sin Lee; Megan O'Grady; Susan Tross; Patrick Wilson; Katherine Elkington (BMC, 2024)
Abstract Background Sexually transmitted infections are a significant, and growing, public health problem in this country - particularly among youth. Innovative strategies are needed to reduce the community burden of infection. Preliminary studies indicate that individuals involved in the criminal legal system have high rates of infection. While gaps exist in providing screening for incarcerated individuals, there are minimal efforts that have been initiated to screen individuals diverted from incarceration. In this study, we examined the STI risk profile and feasibility of screening for sexually transmitted infections for youth who were attending an alternative sentencing program after arrest for a minor offense. Youth were screened for chlamydia and gonorrhea using urine-based nucleic acid amplification tests. Results Of the 307 participants engaged in a program providing supportive services for criminal legal system involved youth at the Brooklyn Court House in New York City, 186 agreed to screening for sexually transmitted infections, and 8% were positive for chlamydia, gonorrhea, or both. Conclusions Screening programs within carceral settings have proven effective in identifying individuals with STIs. However, with policy changes diverting more young people away from incarceration and into community-based programs, innovative programs are needed to identify STIs among youth in these settings. Our findings indicate that it is feasible to conduct venue-based screening in these settings, and, doing so may identify youth in need of treatment and further evaluation.